Bit Plane Complexity Segmentation (BPCS) - Firamawati Hia; Fortina Lumban Gaol; Muhammad Rizqy Aditya Pratama (BIOS: Jurnal Informatika dan Sains, 2026)
Bit Plane Complexity Segmentation (BPCS) is a steganographic method that utilizes the visual complexity characteristics of digital images to embed secret information. This method works by dividing an image into several bit-planes, then measuring the level of complexity of each bit-plane block. Blocks with high complexity are considered similar to noise, making them suitable as a medium for data embedding without causing significant visual changes to the original image. The main advantage of BPCS lies in its large data embedding capacity and high level of security, as the hidden information is difficult to detect through visual observation or simple analysis. Therefore, BPCS becomes an effective solution for securing digital data, particularly in applications such as copyright protection, confidential communication, and information security.